FLEXURAL BEHAVIOR OF COMPOSITE BEAMS WITH CORRUGATE WEB - sarah alamar; Najla’a AL-shareef (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The experimental programs involve testing of five beams with the same length and shear connectors subjected to two concentrated loads. The main objective of this study to investigate the effect of using different types of materials (carbon and galvanized steel) for flat and corrugate web. The corrugate beams have varied the sub-panel fold of a single wave (100-150) mm. Practical results show that the galvanized steel webs have an ultimate flexural capacity lower than that for carbon steel by about (53% and 50%) respectively for flat and corrugate web. The increasing of the wave of sub-panel fold causes significant decreases in flexural capacity by about (5%). Practical results show also that the corrugate web with carbon or galvanized steel exhibited better results as compared with flat web beams in stuffiness ductility and energy absorption.